DENOSUMAB: A NEW ERA IN OSTEOPOROSIS MANAGEMENT IN VIETNAM - Van Tuan, Nguyen; Pham Thuc Lan, Ho (Journal of Health and Aging, 2025)
Osteoporosis is a skeletal disorder characterized by compromised bone strength and increased fracture risk. In Vietnam, the disease affects 30% in postmenopausal women and 10% in men over 50, highlighting a growing public health challenge as the population ages. Bisphosphonates remain the standard firstline treatment. Recent advances in bone biology highlight the critical role of the RANK/RANKL/OPG pathway in bone remodeling. Osteoporosis arises when the RANKL/OPG ratio becomes imbalanced. Denosumab, a monoclonal antibody that targets RANKL, replicates OPG’s ability to suppress osteoclast activity, increasing bone mineral density and reducing fracture risk by 20–68% across various skeletal sites. Unlike bisphosphonates, Denosumab is reversible, metabolized by the reticuloendothelial system, and appropriate for patients with advanced kidney disease, though it necessitates monitoring for hypocalcemia. This advancement offers clinicians a valuable tool for managing osteoporosis in Vietnam.